2008
DOI: 10.1007/s11332-008-0059-1
|View full text |Cite
|
Sign up to set email alerts
|

Motion analysis after total knee arthroplasty

Abstract: The aim of this study is to evaluate the functional performance after total knee replacement (TKR). Two groups of patients, one with mobile (n=9) and one with fixed bearing (n=8) total knee prosthesis, were compared by means of motion analysis. A group of healthy subjects (n=8), matched by age, were used as controls. Kinematics, kinetics and electromyography data were collected during physiological daily activities such as walking and squatting. During walking, both groups of patients showed a speed of progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…Concurrent with the previous research [14], [15], [16] and [17], few biomechanical differences were found between FB and MB prostheses. The FB and MB groups could not be distinguished following an adequate period of rehabilitation at nine months post-surgery [12], [22] and [23], with no parameter reaching significance in the spatiotemporal, kinematic, and kinetic results.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Concurrent with the previous research [14], [15], [16] and [17], few biomechanical differences were found between FB and MB prostheses. The FB and MB groups could not be distinguished following an adequate period of rehabilitation at nine months post-surgery [12], [22] and [23], with no parameter reaching significance in the spatiotemporal, kinematic, and kinetic results.…”
Section: Discussionsupporting
confidence: 76%
“…We also used the same implant manufacturer with the same femoral components, in addition to both prostheses being posterior stabilised with the patella resurfaced, limiting potential confounding factors. The predominant limitation of the current study is that of a small sample size, although comparable to the previous literature [15] and [17]. A power calculation was undertaken at the investigation outset, which suggested a total sample size of 21, inclusive of the FB, MB, and control groups.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations